The Impact of FDI Flows on the Dimensions of Sustainable Development in Algeria - An Econometric Study During the Period 2000-2021 - Ouali, Khawla; Grari, Sabrina; Jallouli, Fayza; Yalouli, Tarek (The journal of contemporary issues in business and government, 2023)
This study aimed to measure the impact of foreign direct investment on the dimensions of sustainable development in Algeria through an econometric study for the period 2000-2021, and in order to achieve the goal, complete the use of the ARDLprogram, based on the independent variable that represents the FDI index, and the dependent variables, which represent development indicators. Sustainable based on World Bank data. Through the analysis, it was found that foreign direct investment negatively affects carbon dioxide emissions in the long and short term, and the flow of foreign direct investment is linked to a positive relationship with GDP in the long and short term, and it was found that there is a significant inverse relationship between foreign direct investment and the unemployment rate in the long and short term, in the previous period in the study sample.